2014
DOI: 10.1016/j.pain.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis between polymorphisms in COMT, ESR1, and GCH1 influences COMT enzyme activity and pain

Abstract: Abnormalities in the enzymatic activity of catechol-O-methyltransferase (COMT) contribute to chronic pain conditions, such as temporomandibular disorders (TMD). Thus, we sought to determine the effects of polymorphisms in COMT and functionally-related pain genes in the COMT pathway (estrogen receptor 1: ESR1, guanosine-5-triphosphate cyclohydrolase 1: GCH1, methylenetetrahydrofolate reductase: MTHFR) on COMT enzymatic activity, musculoskeletal pain, and pain-related intermediate phenotypes among TMD cases and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 67 publications
0
73
0
Order By: Relevance
“…However, they were many SNPs correlated with intermediate phenotypes TMD (Slade et al, 2013; Smith et al, 2011, 2013). On the other hand, polymorphisms of COMT genes, ESR1 genes and GCH1 genes interact to influence the enzymatic activity of catechol-O-methyltransferase, musculoskeletal pain, and mood constituting a phenomenon of epistasis (Smith et al, 2014). The study of CACNA2D1, a gene of interest in the cohort Oppera encoding subunit alpha-2 / delta-1 of voltage dependent calcium channels implicated in neuropathic pain, has a differential expression in the masseter muscles according and sex between women with or without TMD myalgia-type (Godel et al, 2014; Sciote et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, they were many SNPs correlated with intermediate phenotypes TMD (Slade et al, 2013; Smith et al, 2011, 2013). On the other hand, polymorphisms of COMT genes, ESR1 genes and GCH1 genes interact to influence the enzymatic activity of catechol-O-methyltransferase, musculoskeletal pain, and mood constituting a phenomenon of epistasis (Smith et al, 2014). The study of CACNA2D1, a gene of interest in the cohort Oppera encoding subunit alpha-2 / delta-1 of voltage dependent calcium channels implicated in neuropathic pain, has a differential expression in the masseter muscles according and sex between women with or without TMD myalgia-type (Godel et al, 2014; Sciote et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Human genetic association studies have shown that the rs4680 SNP, alone or in combination with other nearby SNPs, is predictive of temporomandibular disorder (TMD) and fibromyalgia onset 107,108 . Subsequent molecular studies demonstrated that these SNPs alter the thermostability and/or structure of the COMT transcript 109 , explaining why patients with functional pain disorders 110112 and exacerbated postoperative pain 113116 exhibit decreased levels of COMT alongside increased levels of catecholamines. Preclinical studies further revealed that elevated levels of epinephrine/norepinephrine resulting from low COMT activity, lead to increased pain through activation of βARs 117,118 .…”
Section: Clinical Relevance Of Functional Gene Regulatory Eventsmentioning
confidence: 99%
“…Patients exhibit increased levels of catecholamines 9-11 alongside diminished activity of catechol-O-methyltransferase (COMT), 12,13 a ubiquitously expressed enzyme that metabolizes catecholamines to their inactive derivatives. 14 Furthermore, functional variants in the COMT gene that reduce COMT activity 13,15,16 are associated with increased susceptibility to FM, 17-21 TMD 22 and experimental pain 22,23 as well as impaired response to treatment. 24,25 It is estimated, based on the frequency of allele variation, that nearly two-thirds of patients with chronic pain disorders possess the low-activity COMT variants.…”
Section: Introductionmentioning
confidence: 99%